Concrete filled FRP–PVC tubular columns used in the construction sector: A review - Bazli, Milad; Bazli, Leila; Rahmani , Roozbeh; Mansoor, Sohail; Ahmadi, Mohammad; Pouriamanesh , Rasul (Journal of Composites and Compounds, 2020)
In recent years, fber-reinforced polymer-polyvinyl chloride (FRP-PVC) tubular columns have been used increasingly in civil engineering applications. Concrete-flled RP-PVC tubes possess high durability, high strengthening performance, satisfactory bond strength, and compressive behavior. It has been observed that these cost-effective tubular columns are promising materials for enhancing strain capacities, strength, and stiffness of structures containing reinforced concrete (RC). These composite tubular columns are composed of FRP and PVC and are used for strengthening concrete. FRP enhances strength capacity while PVC improves the corrosion resistance of concrete piles in harsh environments. This review focuses on the properties of FRP-PVC tubular columns, their application in civil engineering, and the recent advancements in this field.